Resistive‐switching and current‐conduction mechanisms in F8BT polymer resistive switch. (1st November 2016) - Awais, Muhammad N.; Mustafa, Maria; Shehzad, Muhammad N.; Farooq, Umer; Hamayun, Mirza T.; Choi, Kyung H.
Abstract : Poly[(9, 9‐di‐n‐octylfluorenyl‐2, 7‐diyl)‐alt‐(benzo[2, 1, 3]thiadiazol‐4, 8‐diyl)] (F8BT) polymer has been investigated to elucidate the resistive‐switching properties in a sandwiched structure of indium tin oxide (ITO)/F8BT/aluminium (Al). An active layer of F8BT polymer was deposited on the ITO‐coated polyethylene terepthalate through spin coating. Morphologically, the layer was characterised with field emission scanning electron microscope. The fabricated sample showed resistive‐switching properties within ±5 V with an OFF/ON ratio of 10:1. The switching characteristics were attributed to the transition of trap‐limited space charge‐limited conduction (SCLC) to trap‐filled SCLC. It is shown through energy band diagram that memory effects in the fabricated sample were due to the trapping of electrons in the F8BT active layer that were injected from the top Al electrode.